Comparison of glycaemic index of honey and sports energy products - Nives Brekalo; Ines Banjari (Acta Scientiarum. Health Sciences, 2024)
Consumers' interest towards glycaemic index (GI) is expanding due to their aspiration towards informed buying and increased awareness regarding diet. This is especially the case for people engaged in various physical activities. Their diet, besides general principles of a healthy balanced diet, should also meet the needs of training. Consumption of carbohydrates with different GI before, during and after training affects athletic performance, with high GI food being preferred. The aim was to compare the effect of honey and two different sports energy products on glycaemia and their potential in terms of sports performance. GI of acacia honey and two sports energy products (gel and jelly) was determined according to the method ISO 26642: 2010. Ten healthy males aged 23.2 years (20 to 27 years old) who are minimum 4 hours per week engaged in at least one sport were enrolled. Glycaemia was the least affected by honey (GI = 89.6 ± 37.1), while jelly increased glycaemia the most (GI = 162.1 ± 60.9), and the difference was statistically significant (p = 0.008). Honey also showed good acceptability, and did not differ in subjective satiety score to gel or jelly. The results show that honey can be a good alternative to various sports energy products, and a more affordable one.